Engineering technology and applications : proceedings of the 2014 International Conference on Engineering Technology and Applications (ICETA 2014), Tsingtao, China, 29-30 April 2014 - Shao, Fun; Shu, Wise; Tian, Tracy (Balkema Book, 2014)
Engineering Technology and Applications contains the contributions presented at the 2014 International Conference on Engineering Technology and Applications (ICETA 2014, Tsingtao, China, 29-30 April 2014). The book is divided into three main topics:- Civil and environmental engineering- Electrical and computer engineering- Mechanical engineeringConsiderable attention is also paid to big data, cloud computing, neural network algorithms and social network services. The book will be invaluable to professionals and academics in civil, environmental, electrical, computer and mechanical engineering.